Sudden Vision Loss Secondary to Optic Nerve Infiltration as a Presenting Symptom of Metastatic Lung Adenocarcinoma - M. M. Shamim; M. Whaley; H. Rana; S. K. Jeffus; S. Bhatti; A. B. Sallam (Case Reports in Ophthalmological Medicine)
Purpose. To report a rare case of left-sided metastatic optic nerve infiltration and right-sided choroidal mass with exudative retinal detachment caused by EGFR exon 19 deletion positive non-small-cell lung adenocarcinoma that responded to targeted therapy with osimertinib (EGFR-TKI). Our patient demonstrated an excellent response with reduced size of the metastatic choroidal mass of the right orbit and improved visual acuity, in addition to systemic disease control. Case. A 66-year-old male patient with a history of diabetes mellitus, hypertension, and tobacco use presented with sudden vision loss in the left eye secondary to optic nerve infiltration and subacute vision loss in the right eye secondary to exudative retinal detachment from a choroidal metastasis. He was found to have a right lung mass, multiple metastatic pulmonary nodules, and liver and bone metastases. Biopsy from a mediastinal lymph node confirmed the diagnosis of metastatic lung adenocarcinoma. He was found to have exon 19 deletion on next-generation sequencing. We treated him with local radiation therapy to the left eye and systemic osimertinib (EGFR-TKI). Conclusion. To our knowledge, our case is the first report of a patient who initially presented with acute vision loss and was found to have metastatic retrobulbar optic nerve infiltration in one eye and metastatic choroidal lesion with exudative retinal detachment in the fellow eye secondary to lung adenocarcinoma. Due to the rarity of this condition, literature regarding effective treatment is scarce. Our patient demonstrated significant improvement in visual acuity and resolution of exudative retinal detachment in the right eye following osimertinib treatment and radiation therapy to the left eye. Further investigation into the role of tyrosine kinase inhibitors and radiation therapy in treating intraocular metastasis involving the optic nerve is needed.